Features of surgical treatment for gunshot wounds of the heart and great vessels with migration of foreign bodies - I.A. Lurin; E.M. Khoroshun; V.V. Makarov; V.V. Nehoduiko; O.V. Buchnieva; I.V. Veryovkin (Медицина неотложных состояний)
Background. The purpose was to investigate the features of the migration of foreign bodies of gunshot origin when the heart and great vessels are injured. Materials and methods. Eighty-two wounded people were examined who had blind gunshot wounds of different location, were admitted to the Military Medical Clinical Center of the Northern Region between May 2014 and May 2024, and had the phenomenon of migration of foreign bodies of gunshot origin in different directions. Eleven (13.4 %) patients had the foreign body migration through the vascular bed. All the wounded were male, the average age was 34.2 ± 0.4 years. The medical history, data of objective clinical and general clinical and laboratory studies, as well as the results of instrumental diagnosis were studied. Depending on the location of the wound, all the injured were subjected to spiral computed tomography of the head, thoracic organs and abdominal cavity, X-ray of the head, thoracic organs and abdominal cavity, limbs, video bronchoscopy and video gastroduodenoscopy, ultrasound of the neck, chest, abdomen and soft tissues. Patients underwent primary surgical treatment of wounds, suturing the wounds of blood vessels and heart, and removal of foreign bodies. A surgical magnetic instrument was used for diagnosis and removal of ferromagnetic foreign bodies. Results. According to the location of the entrance hole during the migration of a foreign body of gunshot origin, the distribution was as follows: neck — 1 (9.1 %), chest — 4 (36.4 %), abdomen — 5 (45.5 %), extremity — 1 (9.1 %) case. According to the place of the beginning of the foreign body migration through the vascular bed, the distribution was as follows: left jugular vein — 1 (9.1 %), right subclavian vein — 1 (9.1 %), heart — 3 (27.3 %), portal vein — 1 (9.1 %), left renal vein — 1 (9.1 %), right renal vein — 1 (9.1 %), inferior vena cava — 3 (27.3 %), right superficial femoral vein — 1 (9.1 %) case. According to the foreign body fixation during vascular migration, the distribution was as follows: right internal carotid artery — 1 (9.1 %), heart — 3 (27.3 %), right pulmonary artery — 2 (18.2 %), left pulmonary artery — 3 (27.3 %), portal vein branch — 1 (9.1 %) case. By the site of the entrance hole, where migration of a foreign body occurred later, primary surgical treatment was performed in 6 (54.5 %) cases; in 5 (45.5 %) cases, it was not indicated. According to the place of the beginning of the foreign body migration through the vascular bed, the operative interventions were as follows: colotomy on the left, ligation of the jugular vein — 1 (9.1 %), laparotomy, suturing the wound of the portal vein — 1 (9.1 %), laparotomy, suturing the wound of the renal vein — 2 (18.2 %), laparotomy, suturing the inferior vena cava wound — 2 (18.2 %) cases. In 5 (45.5 %) cases, surgery directed to the place of the beginning of migration through the vascular bed was not performed. According to the place of the foreign body fixation during vascular migration, the interventions were as follows: colotomy on the right, arteriotomy, removal of the foreign body, suturing the artery — 1 (9.1 %), thoracotomy, pneumotomy, arteriotomy, removal of the foreign body, suturing the artery — 5 (45.5 %), thoracotomy, dissection of the right atrium, removal of the foreign body, atrial suturing — 3 (27.3 %), laparotomy, venotomy, removal of the foreign body, vein suturing — 1 (9.1 %) case. In one (9.1 %) case, the foreign body was not removed from the branch of the portal vein. In two (18.2 %) cases, repeated surgical interventions were performed for repeated intraoperative migration of a foreign body from one side to another along the system of pulmonary arteries in the scope of thoracotomy, pneumotomy, arteriotomy, removal of a foreign body, and artery suturing. Ten (90.9 %) foreign bodies were removed using a modern magnetic surgical instrument. There were no complications or deaths after operative interventions in case of migration of a foreign body of gunshot origin through the vascular bed. The average bed-day was 21.3 ± 2.1 days. Conclusions. Among all directions of migration of foreign bodies of gunshot origin, 13.4 % of cases occur in the vascular bed, which indicates the rarity of such a course of injury. Abdominal and chest injuries predominate by the site of the entrance hole during the migration of a foreign body of gunshot origin. According to the place of the beginning of the foreign body migration through the vascular bed, cases with damage to the heart and the inferior vena cava predominate. By the location of the foreign body fixation during migration through the vascular bed, cases with fixation of a foreign body in the pulmonary artery and heart prevail. All operative interventions in case of migration of foreign bodies of gunshot origin through the vascular bed are open. When comparing surgeries for the migration of a foreign body of gunshot origin through the vascular bed, interventions by the site of the foreign body fixation prevail over those by the site of the beginning of migration and by the site of the entrance hole.